Hermeneutic Analysis: Making Sense of Symbolic Expressions in Izibongo of King Shaka - Ngema, Vusabantu (Southern African Journal for Folklore Studies, 2021)
A substantial number of scholars have previously documented African praise poems, including those that relate to the Zulu kings and queens. To a large extent, these recordings only focus on the content and structural approach to this genre of orality, with little attention paid to contextual meaning. As such, issues of metaphoric expressions are perpetually ignored, which by their very definition contain the underlying meaning and purpose for the crafting of such poetry. Therefore, this article addresses the problem of hidden meaning in Zulu kings’ praise poems that many writers on the subject have missed. As it has long been established that praise poetry, from a Zulu perspective, was/is a story about the life and times of a particular king, a hermeneutic paradigm was used to conduct an inquiry into the most prominent king in the history of the Zulus—King Shaka, the founder the great Zulu nation. The study reveals that reference to this kind of poetry as “praise” itself is problematic, since the craft was used as an evaluation of the king. It both praised and critiqued the king’s reign. With regard to King Shaka, the study reveals that Shaka was a revolutionary and a freedom fighter, contrary to the popularly held view that he was a brutal despot who went around killing innocent people to satisfy his own ego.